The determinants of rural and urban household poverty in the North West province of South Africa - Serumaga-Zake, Philip; Naudé, Willem (Development Southern Africa, 2002)
Based on standard poverty measures, the extent of poverty in the North West province is on average worse than in South Africa. For instance, the poverty gap ratio for North West is twice that of the South African average, and the FGT index is three times as high. This article therefore aims to identify the determinants of rural and urban poverty in the North West province of South Africa. Using data gathered from a survey of 593 black households across the province, probit model estimates suggest that the major significant determinants of household poverty in both rural and urban areas are education and household size. A difference between rural and urban poverty is, first, that extra female adults in a rural household raise the probability of poverty. Secondly, having a migrant (out) worker as head of the household in rural areas lowers the probability of poverty, while this does not apply to urban households. A sensitivity analysis for the robustness of the results over a range of poverty lines reveals that the impact of education is much stronger for poorer households than for more wealthy households.
Keywords: household poverty; data; sensitivity analysis